Replantation and revascularization of amputated upper limb appendages outcome and predicting the factors influencing the success rates of these procedures in a tertiary hospital: An 8-year retrospective, cross-sectional study - Kamarul, Tunku; Mansor, Azura; Robson, Noor Zurani; Albusaidi, Salim H.H.; Suhaeb, Abdulrazzaq Mahmod; Samsudin, Ely Zarina (SAGE Publications, 2018)
Purpose: Worldwide advances in microsurgery have made salvaging of amputated hand via replantation and revascularization common procedures. The present study examines the outcome of these procedures in a tertiary hospital in Malaysia. Methods: Patients with hand amputation who underwent replantation or revascularization from 2005 to 2012 were identified and reviewed for patient characteristics, amputation characteristics and survival rates. Successfully treated patients were interviewed to assess the functional outcome using Quick Disability of the Arm, Shoulder and Hand (Quick-DASH) questionnaire and Michigan Hand Outcome Questionnaire (MHQ). Statistical analysis was performed to evaluate outcome and elicit predictive factors. Results: Fifty-five patients were enrolled: 37 (67.3%) underwent replantation and 18 (32.7%) underwent revascularization. The overall success rate of 78% (n ¼ 43) was within the range of previously reported data (61.6% to 96.0%). Ischaemic time <6 h provided significantly better survival rates (p < 0.05). Functional outcomes were successfully assessed in 34 patients (79%), at a mean follow-up of 40 months (range 11–93 months). The overall Quick-DASH and MHQ scores were 42.82 + 23.69 and 60.94 + 12.82, respectively. No previous reports of functional outcome were available for comparison. Both Quick-DASH (p ¼ 0.001) and MHQ scores (p < 0.001) were significantly higher for finger injuries, followed by thumb, wrist and palm injuries. Conclusion: Ischaemic time and level of injury are important predictors of success rate of replantation and revascularization of amputated upper limb appendages.